Oxidative stress in the brain and retina after traumatic injury - Ryan, Annie K.; Rich, Wade; Reilly, Matthew A. (Frontiers in Neuroscience, 2023)
The brain and the retina share many physiological similarities, which allows the retina to serve as a model of CNS disease and disorder. In instances of trauma, the eye can even indicate damage to the brain via abnormalities observed such as irregularities in pupillary reflexes in suspected traumatic brain injury (TBI) patients. Elevation of reactive oxygen species (ROS) has been observed in neurodegenerative disorders and in both traumatic optic neuropathy (TON) and in TBI. In a healthy system, ROS play a pivotal role in cellular communication, but in neurodegenerative diseases and post-trauma instances, ROS elevation can exacerbate neurodegeneration in both the brain and the retina. Increased ROS can overwhelm the inherent antioxidant systems which are regulated via mitochondrial processes. The overabundance of ROS can lead to protein, DNA, and other forms of cellular damage which ultimately result in apoptosis. Even though elevated ROS have been observed to be a major cause in the neurodegeneration observed after TON and TBI, many antioxidants therapeutic strategies fail. In order to understand why these therapeutic approaches fail further research into the direct injury cascades must be conducted. Additional therapeutic approaches such as therapeutics capable of anti-inflammatory properties and suppression of other neurodegenerative processes may be needed for the treatment of TON, TBI, and neurodegenerative diseases.